Policy and practice in the assessment of juvenile offenders in public juvenile rehabilitation schools in Kenya. - Wambugu, Beth N.; King’endo, Madrine; Kinyua, Joyce N. (My University, 2015)
Historically assessment of juvenile offenders began during colonial era, when every young people who disobeyed colonial rules of regional zoning, labour provision, and hut tax among others were considered offenders and detrimental to colonial interests. Subsequently, the colonial government sentenced such people to institutional rehabilitation, which employed punitive measures to deter the young offenders from reoffending, thereby protecting the colonial interests. The independent government inherited this system of handling offenders. Generally, juvenile rehabilitation practices in Kenya have undergone paradigm shifts from the punitive disciplinarian, to caritative, egalitarian, and systematic paradigms between 1909 and 1995. On the contrary, policies guiding assessment of offenders have not undergone as much evolution. To date, courts of law still process children in conflict with the law. The court makes a ruling to either release the child or commit the child to rehabilitation or probation care. The main policies on which juvenile rehabilitation anchors on are the Children Act, and Special Needs Education Policy. These policies are largely silent on assessment and do not provide opportunities for diversion of children from the courts. Consequently, every child in conflict with the law is processed through a court of law. The interaction of the child with a law court is labeling and impacts on the rehabilitation outcomes. The paper created a basis for comparing policy versus practice in the assessment of juvenile offenders aiming to shed light on the status quo, and project policy on assessment for diverting children from the courts of law. The study utilized mixed method research approach, which borrowed aspects of both phenomenology and descriptive survey research designs. The findings indicate lack of policy on assessment of offenders, and ineffective assessment procedures and tools.
Keywords: Policy; Practice; Assessment of Juvenile Offenders